Cockroach Infestation and Factors Affecting the Estimation of Cockroach Population in Urban Communities. (26th May 2013) - Shahraki, Gholam Hossein; Parhizkar, Saadat; Nejad, Alireza Raygan Shirazi
Abstract : Cockroach is one of the most important pests in urban communities. This study was conducted to determine the situation of cockroach infestation and effective factors on cockroach trap count in urban communities of Yasuj City in southwestern Iran. In this study cockroach population in 573 sampling units (residential units, official places, and hospitals) was monitored using sticky traps over a five-week trapping period. Occupants of 348 residential units were also questioned (by means of questionnaire) for cockroach infestation in their respective residence. The study shows almost 39% of sampling units were infested by cockroach. Five species from two families had been identified: Blattidae (comprising Blatta orientalis, B. lateralis, and Periplaneta americana ) and Blattellidae (comprising Blattella germanica and Supella longipalpa ). German cockroach, B. germanica, with widespreaddistribution (80% of infested sampling units) showed the highest frequency (96.7%) of trap counts. The expression of the distribution of German cockroach populations and some factors could affect trapping, and population monitoring in an urban community was surveyed. Additionally, affecting some exclusion factors on cockroach infestation was pointed. Rates and source of cockroach infestation were discussed from the viewpoints of the residents.